Preventive Effects of Long-Term Intake of Plant Oils With Different Linoleic Acid/Alpha-Linolenic Acid Ratios on Acute Colitis Mouse Model - Wang, Xianshu; Yue, Hao; Zhang, Haonan; Wan, Lei; Ji, Shuxia; Geng, Chong (Frontiers in Nutrition, 2022)
Objective: To investigate the preventive effects of plant oils with different linoleic acid/alpha-linolenic acid (LA/ALA) ratios against colitis symptoms, and dysbiosis of gut microbiota in acute colitis mouse model. Methods: Sixty male C57BL/6 mice were assigned into six groups (n=10): three groups were fed low-fat diets with low, medium, and high LA/ALA ratios; and three groups were fed with high-fat diets with low, medium, and high LA/ALA ratios. After three months of diet, the mice were exposed to dextran sodium sulfate solution to induce acute colitis. The severity of colitis was estimated by disease activity index (DAI) and histopathological examination. 16S rRNA gene sequencing was used for the analysis of gut microbiota. Results: Plant oils with a lower LA/ALA ratio showed higher alleviating effects on the symptoms of colitis, which were accompanied by the better prebiotic characteristics manifested as effectively inhibiting the abnormal expansion of phylum Proteobacteria and genus Escherichia-Shigella in the gut microbiota of colitis mouse models. Conclusions: A potential IBD prevention strategy of reducing the LA/ALA ratio in the daily consumed plant oils was proposed in this study. Furthermore, based on the optimized LA/ALA ratio, this preventive effect might not be weakened by the high intake of plant oils.